Preliminary Evaluation of Leaf Extracts from Three Zimbabwean Aloe Species as Potential Bio-Stimulants on Tomato (Solanum lycopersicum L.) Health and Yield - Mafuratidze, Rumbidzai; Chatyoka, Anesu I.; Simbanegavi, Michelle A.; Zhou, Fortune N.; Dzvuke, Tinodaishe M.; Sanjobo, Jennifer T.; Mashavakure, Nilton (Plantropica: Journal of Agricultural Science, 2026)
The use of natural bio-stimulants has gained attention over the past few years, aiming to reduce the excessive use of agrochemicals in crop production thus promoting sustainable agriculture. This study aimed to investigate the bio-stimulant potential of foliar-applied aloe leaf extracts on tomato (Solanum lycopersicum L.) health and yield. The study was done over a period of six months at Chinhoyi University of Technology Farm, Zimbabwe. The control involved normal farmer practice using Compound C® fertiliser (6% N: 15% P2O5: 12% K2O), calcium nitrate (15.5% N) and ammonium nitrate (34.5% N) application at 400, 140 and 200 kg ha-1, respectively. Leaf extracts of Aloe barbadensis Miller, A. ferox M., and A. broomii at concentrations of 10 g/L (low), 20 g/L (moderate) and 30 g/L (high) were combined with three inorganic fertilizer application rates (25%, 50% and 75% of normal farmer practice). The results showed that foliar application of aloe leaf extracts at moderate concentrations and fertilization reduced pest-related leaf damage by 60% relative to normal farmer practice. Furthermore, reduction of inorganic fertilizer by 25%-75% in combination with aloe leaf extracts achieved the same yield as normal farmer practice. The findings of this study highlight the potential of aloe leaf extract–based biostimulants, rich in bioactive compounds and nutrient-associated constituents, to sustain tomato yield and enhance resilience to biotic stress. Further studies should focus on optimising aloe leaf extracts in sustainable nutrient pest management in tomato production.